2015
DOI: 10.1097/md.0000000000001671
|View full text |Cite
|
Sign up to set email alerts
|

Nocardia Arthritis

Abstract: Nocardia are Gram-positive filamentous bacteria responsible for infections ranging from opportunistic life-threatening disseminated diseases to chronic skin and soft-tissue infections.Even if virtually all organs can be infected, articular involvement is rare. Therefore, we report 3 recent cases and performed a literature review of cases of Nocardia arthritis in order to describe clinical features, therapeutic challenges, and outcome of these patients.Among 34 patients (31 in the literature plus our 3 cases), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 44 publications
1
4
0
Order By: Relevance
“…Bacteriological analysis revealed that GZ2020 T exhibited positive Gram staining and weak acid-fast staining, and microscopic examination showed that the bacteria tended to be beaded and to have a rod shape with branching filaments (Supplementary Figure 2), which is consistent with the common characteristics of Nocardia [ 1 , 2 , 6 , 25 ]. However, further phylogenetic analysis and physiological examinations ( Figure 4 and Supplementary Tables 1–4) revealed that it belonged to the Nocardia species but was different from known strains, which indicated that GZ2020 T is a novel pathogen.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Bacteriological analysis revealed that GZ2020 T exhibited positive Gram staining and weak acid-fast staining, and microscopic examination showed that the bacteria tended to be beaded and to have a rod shape with branching filaments (Supplementary Figure 2), which is consistent with the common characteristics of Nocardia [ 1 , 2 , 6 , 25 ]. However, further phylogenetic analysis and physiological examinations ( Figure 4 and Supplementary Tables 1–4) revealed that it belonged to the Nocardia species but was different from known strains, which indicated that GZ2020 T is a novel pathogen.…”
Section: Discussionsupporting
confidence: 53%
“…Compared with other pathogens, these bacteria are common pathogens in immunosuppressed patients and can sometimes cause high mortality [ 3 , 4 ]. However, in recent years, an increasing number of reports have indicated that patients with chronic lung diseases (CLDs), such as chronic obstructive pulmonary disease (COPD) and bronchiectasis, can be affected [ 5 , 6 ]. Due to the increasing number of people at risk and the development of molecular diagnostic methods, a gradual increase in the incidence of Nocardia infection has been observed [ 5 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Virtually all organs can be involved in disseminated nocardiosis, leading to thyroid abscess, endophthalmitis, arthritis, liver or kidney abscess, and endocarditis, among others. 2,21 In disseminated disease, 2-deoxy-2-[fluorine-18]fluoro-D-glucose ( 18 F-FDG) positron emission tomography (PET)/CT can be used to assess the extent of invasive nocardiosis and to guide biopsy. 22 As invasive nocardiosis mostly occurs among immunocompromised patients with no specific features, its diagnosis is challenging and requires a comprehensive microbiological workup, sampling all involved organs and eliminating possible differential diagnoses (see later).…”
Section: Dovepressmentioning
confidence: 99%
“…Virtually all organs can be involved in disseminated nocardiosis, leading to thyroid abscess, endophthalmitis, arthritis, liver or kidney abscess, and endocarditis, among others. 2 , 21 In disseminated disease, 2-deoxy-2-[fluorine-18]fluoro-D-glucose ( 18 F-FDG) positron emission tomography (PET)/CT can be used to assess the extent of invasive nocardiosis and to guide biopsy. 22 …”
Section: Disease Presentationmentioning
confidence: 99%
“…Case series data suggest that most episodes are a result of hematogenous dissemination from a pulmonary infection. 2 However, pulmonary nocardiosis is frequently misdiagnosed—occasionally with catastrophic results.…”
Section: Diagnosismentioning
confidence: 99%